Vegetation history of the Polar Urals over the past 24,000 years based on sedaDNA from two well-dated lake archives - L. Topstad; D. Ehrich; H. Haflidason; J.I. Svendsen; J. Mangerud; R.F. Eldegard; C. Regnéll; L. Elliott; M.F. Merkel; I.G. Alsos; Y. Lammers (Quaternary Science Reviews, 2026)

Taxonomic and metabolic diversity of microbial communities in a thermal water stream in Uzbekistan and proposal of two new classes of uncultivated bacteria, Desulfocorpusculia class. nov. and Tepidihabitantia class. nov., named following the rules of SeqCode - Galina B. Slobodkina; Alexander Y. Merkel; Kseniya V. Kondrasheva; Alexandra R. Stroeva; Elizaveta A. Bonch-Osmolovskaya; Kahramon D. Davranov; Alexander I. Slobodkin (Systematic and Applied Microbiology, 2025)

A new type of submarine chimneys built of halite - C. Siebert; D. Ionescu; U. Mallast; S. Merchel; B. Merkel; P. Möller; S. Pavetich; T. Pohl; T. Rödiger; Y. Yechieli (Science of The Total Environment, 2024)

Potential biosignatures in goethite deposits in Mavros Vrachos Quarry hypogene cave - G. Lazaridis; D. Bessas; M. Panou; B. Maróti; W. Crichton; V. Melfos; L. Papadopoulou; S. Gkelis; D.G. Merkel; A.I. Chumakov; P. Voudouris (CATENA, 2024)

Past and future impact of the winter North Atlantic Oscillation in the Caspian Sea catchment area - Sri D. Nandini‐Weiss; Matthias Prange; Klaus Arpe; Ute Merkel; Michael Schulz (International Journal of Climatology, 2020)
The Caspian Sea level (CSL) has undergone variations of more than 3 m during the past century with important implications for the life of coastal people, economy and the ecosystem. The origin of these variations as well as future changes in the Caspian water budget are still a matter of debate. Here, the major modes of North Atlantic winter climate variability and atmospheric teleconnections that have a potential effect on the hydroclimate of the Caspian catchment region are examined. The skill of the Community Earth System Model (CESM1.2.2) regarding the simulation of the modern climatology in the Caspian region and the major North Atlantic modes are analysed using different atmospheric grid resolutions and setups of the atmospheric component, the Community Atmosphere Model (CAM4 and CAM5). CESM1.2.2 with CAM5 atmosphere physics and 1° atmospheric grid resolution shows reasonable skill in simulating the regional Caspian basin climatology and the winter North Atlantic Oscillation (NAO). Using this model version, a weakly positive ( r = .2) statistically significant ( p r = .5, p

Potential misidentifications of two climate indicator species of the marine arctic ecosystem: Calanus glacialis and C. finmarchicus - T. M. Gabrielsen; B. Merkel; J. E. Søreide; E. Johansson-Karlsson; A. Bailey; D. Vogedes; H. Nygård; Ø. Varpe; J. Berge (Polar Biology, 2012)

Structural Characteristics of Renal Glomerular System in ISIAH Rats under Conditions of Chronic Stress and Preventive Hypotensive Drug Therapy - E. E. Filyushina; M. D. Shmerling; V. A. Lazarev; I. I. Buzueva; A. L. Merkel; G. S. Yakobson (Bulletin of Experimental Biology and Medicine, 2011)

Non-invasive stimulation of the vibrissal pad improves recovery of whisking function after simultaneous lesion of the facial and infraorbital nerves in rats - H. Bendella; S. P. Pavlov; M. Grosheva; A. Irintchev; S. K. Angelova; D. Merkel; N. Sinis; K. Kaidoglou; E. Skouras; S. A. Dunlop; Doychin N. Angelov (Experimental Brain Research, 2011)

Low genetic diversity and lack of population structure in the endangered Galápagos penguin (Spheniscus mendiculus) - Benjamin D. Nims; F. Hernán Vargas; Jane Merkel; Patricia G. Parker (Conservation Genetics, 2008)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Fungal disease resistance of Caribbean sea fan corals ( Gorgonia spp.) - K. Kim; C. D. Harvell; P. D. Kim; G. W. Smith; S. M. Merkel (Marine Biology, 2000)